Rhetorical evaluation of seventeenth century prefaces to English treatises on midwifery - Sánchez-Cuervo, Margarita (Adam Mickiewicz University, 2010)
This study tries to offer a rhetorical account of the main arguments and figures encountered in 17th c. English prefaces, dealing with the art of midwifery and the delivery of children. I foreground a main causal argument wherein the author states the necessity for a treatise of this delicate nature and proposes the motives for its requirement. In doing so, some other reasonings support the causation and provide the reader with more evidence for a good performance at childbirth. In addition, the arguments are enhanced by the presence of some figures of communion that contribute to the rhetorical organisation, and help to portray the prologue as an expository discourse. The insistence on complying with the author’s directions, and the urge not to follow some predecessors’ work also suggests the new authority that the early modern English preface writer is acquiring.